Issues and challenges of knowledge management in online open source hardware communities. (13th October 2020) - Dai, Jason Xinghang; Boujut, Jean-François; Pourroy, Franck; Marin, Philippe
Abstract: Knowledge management (KM) is the process of creating, sharing, using and managing the knowledge and information of an organization. In this paper, we investigate KM practices and needs in Open Source Hardware (OSH) communities. The aim is to provide insights into the KM issues and challenges facing these communities. Our analysis is based on interviews carried out with the participants of 22 projects. Interview transcriptions were coded and tagged with concepts extracted from the literature. Text mining was used to uncover the main concepts embedded in the corpus. From this analysis, knowledge sharing emerged as one of the top-rated concepts. Codification and personalization also proved to be important KM approaches, both requiring support in the OSH design process. Using a dendrogram, we highlighted the benefits and challenges of codification together with some interesting concept associations. High contributor turnover, little or no standardization and weak project structuring are still key challenges for OSH communities when it comes to ensuring awareness, making decisions and sharing knowledge.